Subclinical personal correlates of psychological safety - Zhuravlova , Larysa Petrivna; Lytvynchuk , Alla Ivanivna; Grechukha , Iryna Anatoliivna; Bedny , Inna Semenivna (Insight: the psychological dimensions of society, 2023)
The critical transformations of modern society, when personal and public safety can be sharply and suddenly lost, and “negative” (destructive, subclinical, antisocial) personality traits have sources of development, makes it necessary to determine the peculiarities of the relationships between these phenomena. In recent years, the study of the dark sides of the personality, known as the “dark core”, has become increasingly relevant. The purpose of the article is to study the psychological features of the subjective feeling of personal safety in the conditions of the Covid-19 pandemic. Methods. The “Dark Triad” questionnaire (D. L Paulhus & K. M. Williams) and the author’s methodology were used to achieve the research goals. To investigate subclinical personal correlates, the short scale of Paulhus D. L. & Williams K. M. (2010) questionnaire, which allows determining a person’s tendency to manifest one of the personal constructs of the dark triad(machiavellianism, narcissism, and psychopathy) was used. In order to build a psycholinguistic model of human danger and research the levels of personal safety in various spheres of life, a collective author’s methodology was applied (Zhuravlova et al., 2020, 2022). The methodology consists of three parts: a) general information; b) associative scale;c) tasks aimed at determining feelings of personal security in physical, sexual, gender, family, territorial, financial, religious, national, political, social, food availability, and business spheres of life. Results. An empirical structural phenomenological psycholinguistic model of human danger has been built. The emotional, cognitive and behavioral components of the model are singled out. Significant (p≤.05)difference between the phenomenological characteristics of the subjective associative images of the danger of “machiavellians”, “narcissists” and “psychopaths” were established. Machiavellianism (cynicism, the desire for manipulative influence on other people and the need for control), narcissism (egocentrism, pathological self-love)and psychopathy (antisociality, emotional coldness) do not have significant correlation with feelings of personal security. In general, the average value of the integral level of security of the respondents in the conditions of the Covid-19 pandemic is quite high. Significant difference was found between indicators of the subjective sense of security of the respondents with a high, medium and low level of manifestation of dark personality traits only in the political sphere of life (p = .032). Conclusions. The empirical structural-phenomenological psycholinguistic model of human danger has a three-component structure. There is a difference between the surface (conscious) and deep (subconscious) phenomenological characteristics of the subjective associative images of the danger for an individual. The former are characterized by the dominance of cognitive and emotional personal correlates, and the latter – by behavioral ones. The integral level of personal safety of Ukrainian citizens in the conditions of the Covid-19 pandemic is quite high. There is no reliable correlation between indicators of subclinical personality traits and its integral psychological safety, except for safety in the political sphere.